Electrical Conductivity and Ion Pair Formation of S-Acetylthiocholine Halides and Perchlorate in Ethanol - Water At 25 Oc. - N. H. EL – HAMMAMY; A. I. KAWANA; M. F. AMIRA; N. S. EL – SISY (International Journal of Pharma and Bio Sciences, 2010)
The conductance of s-acetylthiocholine halides and perchlorate has been measured in ethanol – water mixtures (28.6 < D < 72.0). The conductance parameters derived from Fuoss – Onsager conductance theory indicate that the solvation of halides and perchlorate decreases with the decrease of the dielectric constants until a certain minimum and then increases again. The plot of log kA vs. 1/D is found to be non linear indicating that the equation of association cannot be applied. The association constant is analyzed using the solvent separated – ion pair model.